An Analysis of the Librarian's Role at the UPA Library of the University of Bengkulu as Information Specialists in the Digital Knowledge Ecosystem - Alfiyah; Purwaka; Aang Gunaidi (Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
Librarians, as information specialists, play a vital role in managing and providing access to digital libraries. Despite the availability of digital information through repositories and digital libraries, a gap remains between users and their effective utilization. This underscores the importance of librarians in facilitating access and supporting users. This study analyzes the role, competencies, and challenges faced by librarians at the UPA Library of the University of Bengkulu in the digital knowledge ecosystem. A qualitative descriptive approach was used, with data collected through semi-structured interviews with four librarians and two users, direct observation, and documentation. Data were analyzed using data reduction, presentation, and conclusion drawing. The findings show that librarians act as information specialists by providing access through the OPAC system, repositories, digital libraries, e-journals, Springer Digital References, Instagram, and the library website. They evaluate and ensure credible digital information sources, preserve and back up collections, and assist users in information searches. However, librarians face challenges such as budget constraints, low user awareness, limited human resources, network issues, restricted access, and inadequate collections. These findings contribute to understanding the role of librarians as information specialists.